2012
DOI: 10.1093/bib/bbs052
|View full text |Cite
|
Sign up to set email alerts
|

Assessing protein conformational sampling methods based on bivariate lag-distributions of backbone angles

Abstract: Despite considerable progress in the past decades, protein structure prediction remains one of the major unsolved problems in computational biology. Angular-sampling-based methods have been extensively studied recently due to their ability to capture the continuous conformational space of protein structures. The literature has focused on using a variety of parametric models of the sequential dependencies between angle pairs along the protein chains. In this article, we present a thorough review of angular-samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…Such experiment settings are balanced between the accuracy and the speed of our protein structure alignment algorithm because only a minor improvement on accuracy is gained by increasing the sizes, while slowing down the running time. The local fragment size of 9 was previously shown to be the optimal balance between the complexity of the model and the amount of data required to train the model [35,36]. Other experiment settings remained the same as in the previous experiment.…”
Section: Scoring Function Evaluation On Consistency With Eye-examed Amentioning
confidence: 99%
“…Such experiment settings are balanced between the accuracy and the speed of our protein structure alignment algorithm because only a minor improvement on accuracy is gained by increasing the sizes, while slowing down the running time. The local fragment size of 9 was previously shown to be the optimal balance between the complexity of the model and the amount of data required to train the model [35,36]. Other experiment settings remained the same as in the previous experiment.…”
Section: Scoring Function Evaluation On Consistency With Eye-examed Amentioning
confidence: 99%
“…To take into account the circular nature of the angular data, Maadooliat et al (2013a) suggested the following modified bivariate kernel estimator…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Although most problems in the protein structure field depend on coordinate-based methods, backbone-angle-based methods have provided an attractive alternative approach in various protein structure-related problems, such as protein structure prediction (Simons et al, 1999;Hamelryck et al, 2006;Boomsma et al, 2008;Zhao et al, 2010), protein loop modeling (Ting et al, 2010), model quality assessment (Benkert et al, 2008;Gao et al, 2009;Archie and Karplus, 2009), prediction server ranking (Qiu et al, 2008;Maadooliat et al, 2013a), protein structure alignment (Miao et al, 2008;Challis and Schmidler, 2012), free energy function learning (Mu et al, 2005;Altis et al, 2008;Riccardi et al, 2009), and molecular dynamics simulation (Altis et al, 2007). In this paper, we focus on statistical modeling of the bivariate distribution of protein backbone angles.…”
Section: Introductionmentioning
confidence: 99%
“…The list of popular scoring functions includes root mean squared deviation (RMSD), MaxSub score [21], TM-score [34], GDT-TS and GDT-HA scores [32], and LagSVDi [15]. Unfortunately, methods, to optimize the TM-score and the GDT-TS/GDT-HA score, are either unknown or with high time complexity.…”
Section: Introductionmentioning
confidence: 99%